Is there a problem with tourist use housing? - José Ramón Cardona; Onofre Martorell Cunill; Alberto Prado Román; Antoni Serra Cantallops (European Research on Management and Business Economics (ERMBE), 2021)
In the last five years, home rentals for tourists have generated significant media and social concern. Since the economic crisis of 2007-2008, online platforms have emerged that have boosted the collaborative economy and provided security and trust. There are two positions related to the impacts of peer-to-peer and intermediation platforms: some consider them to reflect the destruction of tourist destinations at the hands of international corporations, while others allege that they have helped improve the incomes of many families and meet demand. These positions raise doubts, and based on the descriptive analysis of secondary public data from Spain, this study makes a first approximation of the actual situation. The results indicate that the platforms have given online visibility to business that already existed, while tourist rentals cater to specific market niches and adjust hotel supply to tourist demand. The study concludes that tourist rentals have been confused with the real problem: large and rapid increases in demand that are difficult to manage, aggravating mismatches in the rental market that are the result of multiple factors.
Keywords: L83; L85; R21; Z30; 650; P2P Accommodation; Tourist rentals; Spain; Ibiza and formentera